Can seeking happiness make people unhappy? Paradoxical effects of valuing happiness. - Iris B. Mauss; Maya Tamir; Craig L. Anderson; Nicole S. Savino (2011)
Happiness is a key ingredient of well-being.It is thus reasonable to expect that valuing happiness will have beneficial outcomes.We argue that this may not always be the case.Instead, valuing happiness could be self-defeating because the more people value happiness, the more likely they will feel disappointed.This should apply particularly in positive situations, in which people have every reason to be happy.Two studies support this hypothesis.In Study 1, female participants who valued happiness more (vs.less) reported lower happiness when under conditions of low, but not high, life stress.In Study 2, compared to a control group, female participants who were experimentally induced to value happiness reacted less positively to a happy, but not a sad, emotion induction.This effect was mediated by participants' disappointment at their own feelings.Paradoxically, therefore, valuing happiness may lead people to be less happy just when happiness is within reach.Those only are happy who have their minds xed on some object other than their own happiness --Mill, 1873, p. 100Happiness is a crucial ingredient of human well-being and health (Duckworth, Steen, & Seligman, 2005;Fredrickson, 1998;Lyubomirsky, King, & Diener, 2005) and, therefore, people generally value happiness (Diener, 2000;Myers, 2000).Indeed, in an acknowledgment of its value, the pursuit of happiness was identified as an "inalienable right" in the US Declaration of Independence.However, there is substantial variation in the extent to which people value happiness (Eid & Diener, 2001).Whereas some view it as a nice thing to have every now and then, others see it as the sine qua non of their existence.The current investigation examines how such differences in valuing happiness affect people's actual happiness and well-being.We based our operationalization of happiness on a prominent definition in the present cultural context, namely individuals' emotional state (cf.Diener, 2000;Kahneman, Diener, & Schwarz, 1999).At first glance, valuing happiness should lead to positive outcomes, because it is assumed that the more one values happiness the happier one will be.Models of goal pursuit (e.g., Mischel, Cantor, & Feldman, 1996) generally back up this intuition.